Level of Interest and Career Opportunities as Functional Officials for the Management of Goods/Services Procurement in the Government of East Kalimantan Province - Musdamang Musdamang; Roni Ekha Putera; Eha Saleha (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
The low fulfilment of the Functional Position of Goods/Services Procurement Officer (JF PPBJ) amid substantial procurement budgets poses a challenge to accountable government administration. This study analyses the low career interest and opportunities of State Civil Apparatus (ASN) to become JF PPBJ within the East Kalimantan Provincial Government by integrating psychological and managerial perspectives. Using a mixed-methods explanatory sequential design, quantitative data were collected from 92 respondents through Likert-scale questionnaires and analysed using multiple linear regression with SPSS, while qualitative data were obtained from interviews, focus group discussions with 20 key informants, observations, and documentation, then analysed using the Miles and Huberman model with NVivo 15. The results show that attitude, subjective norms, perceived behavioural control, and loss aversion simultaneously influenced ASN career interest. Partially, perceived behavioural control had a significant positive effect, while loss aversion had a significant negative effect; attitude and subjective norms were not significant. Qualitative findings revealed that low interest was shaped by workload, regulatory dynamics, compensation, legal risks, competency standards, career uncertainty, comfort zones, and managerial barriers. The study concludes that career interest is strongly influenced by self-efficacy, status quo bias, and goal congruence across work units.